2017
DOI: 10.1679/aohc.77.25
|View full text |Cite
|
Sign up to set email alerts
|

<b>Phosphorylation and dephosphorylation of aquaporin-2 at serine 269 and its subcellular distribution during vasopressin-induced exocytosis and subsequent endocytosis in the rat </b><b>kidney </b>

Abstract: Summary. Aquaporin-2 (AQP2) is a water channel protein that is trafficked between intracellular vesiclesand the plasma membrane of kidney collecting duct cells upon vasopressin stimulation. Vasopressin changes the phosphorylation states of the AQP2 C-terminal serines (Sers), Ser256, Ser261, Ser264, and Ser269, in rats and mice, which is thought to play a role in controlling trafficking. Here, we focused on Ser269. We developed a specific antibody to Ser269-phosphorylated AQP2. Using immunofluorescence microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As it has been reported that phosphorylation of Ser-269 is involved in the apical membrane retention of AQP2 (23), we also examined the Ser-269-phosphorylated form of AQP2 in urinary exosomes after renal I/R. The specificity of the antibody used in this experiment has been verified (40). As shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As it has been reported that phosphorylation of Ser-269 is involved in the apical membrane retention of AQP2 (23), we also examined the Ser-269-phosphorylated form of AQP2 in urinary exosomes after renal I/R. The specificity of the antibody used in this experiment has been verified (40). As shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Specificity of the anti-pSer-256 antibody demonstrated by immunohistochemistry. A-C: to investigate the specificity of anti-Ser-256-phosphorylated AQP2 antibody (pSer-256Ab), peptide preadsorption was performed on kidney sections (same sample as in Ref 40…”
mentioning
confidence: 99%